Fermented plant-based beverage supplemented with uvaia (Eugenia pyriformis) pulp: an innovative and pioneering approach to diversify plant-based diet product market - Santana de Oliveira, Thaísa; Sant’Anna, Roblessa; Arend, Giordana Demaman; Sorita, Guilherme Dallarmi; Camelo-Silva, Callebe; Hoff, Rodrigo Barcellos; Verruck, Silvani (Frontiers in Food Science and Technology, 2024)
Over the years, there has been an increase in demand for plant-based foods as alternatives.In line with this, this work explores the production and in vitro digestion of a fermented plant-based beverage (FPBB) produced with pea and rice proteins and 0% (FPBB-C), 5% (FPBB-5), and 10% (FPBB-10) uvaia pulp through lactic fermentation with Lacticaseibacillus rhamnosus GG. The in vitro gastrointestinal digestion process was conducted to assess the bioaccessibility of L. rhamnosus GG, total phenolic content (TPC), and antioxidant activity before and after simulating the gastrointestinal conditions.After 48 hours of digestion, highly viable L. rhamnosus GG cells remained throughout the gastrointestinal system. FPBB-C (106.89%) and FPBB-5 (109.38%) exhibited higher survival rates than FPBB-10 (102.20%), indicating that these beverages have a higher prebiotic action potential. Compared with the non-digested samples, after 48 h of digestion, all samples exhibited a significant increase in TPC. The same behavior occurs for the antioxidant activity of FPBB-C, FPBB-5, and FPBB-10 by DPPH (4.06, 3.96, and 8.44 mg TEAC mL -1 ), ABTS (10.28, 11.06, 11.97 mg TEAC mL -1 ), and FRAP method (917.02, 863.87, and 1983.23 mg TEAC mL -1 ). Thirteen compounds were identified and quantified in uvaia pulp by HPLC-DAD-ESI-MS, particularly epigallocatechin gallate, quercetin-3-rhamnose, and quercetin-3-glucoside. Isorhamnetin was the main phenolic compound detected in the colon, assumably due to the conversion of quercetin-3glucoside by the probiotic cells. In conclusion, as all counts were above 9 log CFU g -1 , the FPBB formulations containing pea, rice protein, and uvaia pulp become a promising vehicle for carrying L. rhamnosus GG.